There's No Crying in Business - Rivera, R. author. aut Link
IX, 178 p.
Keywords: Based on interviews with women academics, engineers, politicians, mathematicians, neurologists and others in male dominated organizations as well as the author's own experiences, this book will offer insights and advice to women who aspire to top positions in companies and industries where men traditionally have held those positions.